2010
DOI: 10.1158/1940-6207.capr-09-0196
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Combined Phytochemicals and Skin Cancer Prevention in SENCAR Mice

Abstract: The purpose of our study was to determine the inhibitory effect of combined phytochemicals on chemically induced murine skin tumorigenesis. Our hypothesis was that concurrent topical and dietary treatment with selected compounds would lead to more efficient prevention of skin cancer. We tested ellagic acid and calcium D-glucarate as components of diets, while resveratrol was applied topically; grape seed extract was applied topically or in the diet. The 4-week inflammatory-hyperplasia assay based on the 7,12-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 35 publications
1
47
0
1
Order By: Relevance
“…64,74,[77][78][79][80][81][82][83] Seed polyphenols and extracts in particular were shown to inhibit 7,12-dimethylbenz[a]anthracene (DMBA)-initiated and 12-O-tetradecanoylphorbol-13-acetate (TPA)-promoted tumors in mouse skin; both dermal application and dietary administration had significant inhibitory activity. 74,79,80,82,84 Dietary grape seed extract also inhibited UVinitiated, UV-promoted, or UV-initiated and promoted skin tumors in hairless mice, 64 and it inhibited the formation of azoxymethane (AOM)-induced aberrant crypt foci (ACF) in the intestines of rats. 83 Some of the studies summarized in Table 11 examined the effect of applying DMBA to mice and then later either treating the animals topically or in the diet with grape seed extract without TPA.…”
Section: Tumor Promotionmentioning
confidence: 99%
“…64,74,[77][78][79][80][81][82][83] Seed polyphenols and extracts in particular were shown to inhibit 7,12-dimethylbenz[a]anthracene (DMBA)-initiated and 12-O-tetradecanoylphorbol-13-acetate (TPA)-promoted tumors in mouse skin; both dermal application and dietary administration had significant inhibitory activity. 74,79,80,82,84 Dietary grape seed extract also inhibited UVinitiated, UV-promoted, or UV-initiated and promoted skin tumors in hairless mice, 64 and it inhibited the formation of azoxymethane (AOM)-induced aberrant crypt foci (ACF) in the intestines of rats. 83 Some of the studies summarized in Table 11 examined the effect of applying DMBA to mice and then later either treating the animals topically or in the diet with grape seed extract without TPA.…”
Section: Tumor Promotionmentioning
confidence: 99%
“…GSSE also protects against hepatic ischemia-reperfusion injury (Sehirli et al, 2008), biliary obstruction (Dulundu et al, 2007), and azathioprineinduced hepatotoxicity in rats (El-Ashmawy et al, 2010). More specifically, resveratrol is multi-organ protective owing to its anti-oxidant (Kelen and Tepe, 2007) and anti-inflammatory properties (Kowalczyk et al, 2010). Proanthocyanidins exert antineoplasic effects by inducing cytotoxicity towards some cancer cells (Chatelain et al, 2011), by cell cycle arrest and induction of apoptosis (Kaur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, similar combination had successfully maintained the Cell Biochem Biophys normal levels of essential trace element zinc during lung carcinogenesis [7]. Kowalczyk et al evaluated combination of ellagic acid found in green tea extract and resveratrol present in grapes against skin cancer in mice [14].…”
Section: Advantages Of Overlapping Mechanisms In Multi-agent Chemoprementioning
confidence: 99%